2009
DOI: 10.1007/s11661-009-9948-4
|View full text |Cite
|
Sign up to set email alerts
|

Aging Characteristics of Sn-Ag Eutectic Solder Alloy with the Addition of Cu, In, and Mn

Abstract: In the present investigation, three types of solder alloy, i.e., Sn-Ag-Cu, Sn-Ag-In, and Sn-Ag-Cu-Mn, have been prepared and joined with Cu substrate. In the reflowed condition, the joint interface is decorated with Cu 6 Sn 5 intermetallic in all cases. During aging at 100°C for 50 to 200 hours, Cu 3 Sn formation took place in the diffusion zone of the Sn-Ag-Cu and Sn-Ag-In vs Cu assembly, which was not observed for the Sn-Ag-Cu-Mn vs Cu joint. Aging also leads to enhancement in the width of reaction layers; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Apart from reducing the thickness of the Cu 3 Sn layer, the formation of Kirkendall voids was also suppressed in the SAC305/Cu-2Mn solder joint. Segregation of minor alloying elements at the solder/substrate interface was also observed by Ghosh et al, 21 who reported that the formation of Cu 3 Sn was hindered and the growth of existing Cu 6 Sn 5 became sluggish during aging when Mn was added to Sn-Ag-Cu solder. X-ray elemental mapping in this study revealed that Mn suppressed the growth of Cu 3 Sn directly through segregation in the IMC.…”
Section: Mechanism Of Suppressing Cu 3 Sn Growth and Kirkendall Voidssupporting
confidence: 63%
“…Apart from reducing the thickness of the Cu 3 Sn layer, the formation of Kirkendall voids was also suppressed in the SAC305/Cu-2Mn solder joint. Segregation of minor alloying elements at the solder/substrate interface was also observed by Ghosh et al, 21 who reported that the formation of Cu 3 Sn was hindered and the growth of existing Cu 6 Sn 5 became sluggish during aging when Mn was added to Sn-Ag-Cu solder. X-ray elemental mapping in this study revealed that Mn suppressed the growth of Cu 3 Sn directly through segregation in the IMC.…”
Section: Mechanism Of Suppressing Cu 3 Sn Growth and Kirkendall Voidssupporting
confidence: 63%
“…Analyses of recorded XRD patterns obtained from different zones (layers) across the interface further confirms the presence of different intermetallic phases having a stoichiometry of Cu 3 Sn (ε‐phase orthorhombic) and Cu 6 Sn 5 (η‐phase monoclinic) along with the β‐Sn phase (BCT) for both the solder joints. Kar et al [ 32 ] and Ghosh et al [ 33 ] in their previous studies also found the presence of similar intermetallics phases for other types of solder joints.…”
Section: Resultsmentioning
confidence: 75%
“…During aging process, the growth of IMC layer in SnAgCu/Cu was faster than that of SnAgCuMn/Cu. Mn addition promoted the nucleation of b-Sn and Cu 6 Sn 5 since it provided nucleation sites for b-Sn in alloys matrixes and Cu 6 Sn 5 in reaction layers [14]. The addition of Mn reduced the supercooling degree of solder alloys and coarsened the grain of dendrite Sn and IMCs in the interface significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Lin et al [13] reported that alloying of Mn and Ti dramatically decreased the under cooling of solder alloys, extended volume fraction of proeutectic Sn, formed heterogeneous IMCs (MnSn 2 and Ti 2 Sn 3 ) and changed the morphology and distribution of eutectic IMCs. Ghosh et al [14,15] explored the effects of Cu, In and Mn additions on the properties of the SnAg eutectic solder alloy. The results showed that the additions of either Cu or Cu-Mn had negligible effects on the melting point of Sn3.5Ag solder alloy.…”
Section: Introductionmentioning
confidence: 99%